2005
DOI: 10.1111/j.1399-6576.2004.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Motor nerve blockade potency and toxicity of non‐racemic bupivacaine in rats

Abstract: The potency of S(-) bupivacaine to block the motor activity in the sciatic nerve was enhanced when 25% of the S(-) isomer was replaced by the antipode R(+) bupivacaine. This effect was not associated with increased toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
1
13
0
3
Order By: Relevance
“…The present study confirmed the myocardial contractile dysfunction caused by potent LA 2,8,13,14 . Developed tension and maximum rate of tension development were both decreased more intensely with 100 mM racemic bupivacaine in relation to other LA in this study (Figures 2 and 4).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The present study confirmed the myocardial contractile dysfunction caused by potent LA 2,8,13,14 . Developed tension and maximum rate of tension development were both decreased more intensely with 100 mM racemic bupivacaine in relation to other LA in this study (Figures 2 and 4).…”
Section: Discussionsupporting
confidence: 76%
“…Adding 25% of the R isomer to S(-)bupivacaine (S75/R25) promoted stronger muscle relaxation and motor nerve blockade than bupivacaine isomers alone 13 . However, the effects of non-racemic bupivacaine (S75/R25) on myocardial contractile function remain understudied.…”
Section: Introductionmentioning
confidence: 99%
“…The difference was due to R (+) enantiomer of bupivacaine exerting a synergistic effect on binding characteristics of S (-) enantiomer of bupivacaine to the motor nerves and in their absence binding is less and effect terminates earlier. (20) Locatelli et al (10) because of the delayed surgical duration (31 ± 23 minutes) had a statistically significant differentiation between the groups. Modified Bromage score 0 at wakeup with Bupivacaine vs. Levobupivacaine was 28% vs. 67%, (p= 0.01).…”
Section: Discussionmentioning
confidence: 94%
“…duration, 0.2 Hz frequency) by a pair of platinum electrodes connected to a stimulator (Astromed Grass Model S88). The nerve branch innervating the gastrocnemius muscle was selectively preserved and the tendon of this muscle exposed and tightly connected to a force transducer (Grass FT 03) for isometric tension recording (Astromed Grass, Model 7400) [14]. Muscle twitches were recorded prior to and after incremental bolus injection of azumolene or dantrolene sodium at total doses of 0.5, 1, 2.5, 5 and 7.5 mg/kg.…”
Section: Methodsmentioning
confidence: 99%